Assessment of Chronic Disease Prevalence, Nutritional Habits and Healthy Lifestyle Behaviors in Elderly Patients - Aydin Avci, I.A.; Nal, B.; Ayyildiz, M. (Mattioli 1885 S.p.A. edit@mattioli1885.com, 2016)
Objective: This study aims to determine chronic disease prevalence, nutritional habits and healthy lifestyle behaviors of elderly individuals. Design: Correlational descriptive study. Setting: This study was conducted at a State Hospital between July and October 2014. Participants: A total of 125 elderly people aged 65 and up that came to the hospital between these dates, received inpatient treatment, Sampling was not performed in the study. Measurements: Data collection was accomplished using the "Health Lifestyle Behavior Scale II" with a form comprising 19 questions about participants' demographic features, current diseases and nutritional conditions. Required permissions were obtained from the relevant authorities in order to conduct the study. Re-sults: The average age of the participants was 73±6.22 (min=65, max=91) and the average body mass index was 26.79±3.25. When the participants' weight was examined in terms of body mass index; 61.6% were overweight, 28% were at a normal weight, 8% were class I obese and 2.4% were class II obese. The most frequently observed health problem in the elderly individuals was hypertension with a rate of 65.6%, followed by diabetes at 50.4% and visual impairments at 44.8%. HLBS scale score average was found to be 117.61 ± 17.64 and the general scale total score was close to the lower limit. Conclusion: It was found that the prevalence of hypertension and diabetes was high among the participants. Also, they were determined to be overweight or higher on the BMI scale. An increasingly sedentary lifestyle and slowing of the metabolism can lead to weight gain in old age.
Keywords: Chronic Disease; Elderly Patients; Nutritional Habit